The Growing Evidence for the Importance of the Otoliths in Spatial Memory - Smith, Paul F. (Frontiers in Neural Circuits, 2019)
Many studies have demonstrated that vestibular sensory input is important for spatial learning and memory. However, it has been unclear what contributions the different parts of the vestibular system – the semi-circular canals and otoliths – make to these processes. The advent of mutant otolith-deficient mice has made it possible to isolate the relative contributions of the otoliths, the utricle and saccule. A number of studies have now indicated that the loss of otolithic function impairs normal spatial memory and also impairs the normal function of head direction cells in the thalamus and place cells in the hippocampus. Epidemiological studies have also provided evidence that spatial memory impairment with aging, may be linked to saccular function. The otoliths may be important in spatial cognition because of their evolutionary age as a sensory detector of orientation and the fact that velocity storage is important to the way that the brain encodes its place in space.